NILAI-NILAI PENDIDIKAN PADA AYAT-AYAT TASYBIH DALAM SURAH AL-BAQARAH: (Analisi Ilmu Bayán) - arkal, arkal; Kasim, Amrah; Abunawas, Kamaluddin (ISTIQRA: Jurnal Hasil Penelitian, 2022)
This research specifically examines the use of language styles contained in QS Al-Baqarah to conclude the educational values in that surah. The research method used in this research is qualitative with a library research approach. Meanwhile, data sources are primary data and secondary data. The data collection method is appropriate to the subject of the study and then filtered and translated into theoretical thinking. The research results show that the educational values in the tasybīh verse contained in QS.2 17-19 are the values of faith, monotheism, and obedience. Every aspect of education contains several basic elements that lead to the understanding and practice of Islam, namely faith, monotheism, and obedience